Expert evaluation of traffic signs: conventional vs. alternative designs. Issue 6 (3rd June 2019) - Ben-Bassat, Tamar; Shinar, David; Almqvist, Raquel; Caird, Jeff K.; Dewar, Robert E.; Lehtonen, Esko; Salmon, Paul M.; Sinclair, Marion; Summala, Heikki; Zakowska, Lidia; Liberman, Gabriel
Abstract: Traffic sign comprehension is significantly affected by their compliance with ergonomics design principles. Despite the UN Convention, designs vary among countries. The goal of this study was to establish theoretical and methodological bases for evaluating the design of conventional and alternative signs. Thirty-one conventional signs and 1–3 alternatives for each conventional sign were evaluated for their compliance with three ergonomics guidelines for sign design: physical and conceptual compatibility, familiarity and standardisation. Twenty-seven human factors and ergonomics experts from 10 countries evaluated the signs relative to their compliance with the guidelines. Analysis of variance across alternatives revealed that for 19 of the 31 signs, an alternative design received a significantly higher rating in its ergonomics design than the conventional sign with the same meaning. We also found a very high correlation between the experts' ratings and comprehension from previous studies. In conclusion, many countries use signs for which better alternative designs exist, and therefore UN Convention signs should be re-examined, and ergonomics experts evaluation can serve as a good surrogate for road users' comprehension surveys. Practitioner summary: This study presents theoretical and methodological bases for evaluating the design of UN Conventional and alternative traffic signs. Human factors and ergonomics experts evaluated 31 conventional and 68 alternative road signs, based on ergonomics principles for sign design. Results indicated the need to re-examine poorly designed UN Convention signs.